EFEKTIVITAS EDUKASI PEMANFAATAN JAHE (Zingibber Officinale) UNTUK ANTI INFLAMASI POST PEMASANGAN IMPLAN PADA CALON AKSEPTOR DI DESA BANGSRI KARANGANYAR - Remedina, Gipfel; Mahmudah, Mutik (Jurnal Ilmiah Maternal, 2025)
The Family Planning Program (KB) is one of the strategic efforts to reduce birth rates and improve the health quality of mothers and families. One of the most widely used long-term contraceptive methods is the implant. The inflammatory response after implant insertion is a physiological reaction of the body to tissue trauma caused by the incision. If not properly managed, these complaints can cause anxiety, reduce comfort, and potentially affect the satisfaction and continuity of implant use among prospective acceptors. Ginger contains active compounds such as gingerol, shogaol, and zingerone, which have anti-inflammatory, analgesic, and antioxidant effects. Education on the use of ginger as a supportive therapy after implant insertion can be a safe, inexpensive, and easy-to-apply non-pharmacological alternative for the community. The purpose of this study was to determine the effectiveness of education on the use of ginger for post-implant anti-inflammatory purposes among prospective implant contraceptive acceptors in Bangsri Village, Karanganyar. This study used a quasi-experimental design with a one-group pre-test and post-test design. The sample consisted of 17 prospective implant contraceptive acceptors using total sampling. The intervention consisted of counseling on the use of ginger for anti-inflammation after implant placement. Data were collected using a questionnaire. Analysis was performed using a t-test (paired t-test). The results of the study showed that before education, most respondents (41.2%) had insufficient knowledge. After the intervention, there was a significant increase, with 64.7% of respondents having good knowledge. The average knowledge score increased from 56.47 to 82.94 (p=0.000). The conclusion of the study is that providing education on the use of ginger for anti-inflammatory purposes after IUD insertion can increase mothers' knowledge of non-pharmacological treatments. Support from health workers, cadres, and families is needed in providing health information.